Isolation and Genetic Characterization of Emerging H3N2 Canine Influenza Virus in Guangdong Province, Southern China, 2018–2021 - Ou, Jiajun; Zheng, Feiyan; Cheng, Jiaojiao; Ye, Shaotang S.; Ye, Cundong; Jia, Kun; Lu, Gang; Li, Shoujun (Frontiers in Veterinary Science, 2022)
H3N2 canine influenza virus (CIV) emerged in dogs in China or Korea around 2005 and was first reported in 2008. In 2015, H3N2 CIV was detected in the United States and caused a huge outbreak. To date, H3N2 CIV is continuously circulating in dog populations in China, Korea, and the United States. For continuous monitoring of H3N2 CIV in China, we collected 180 dog nasal swab samples and 196 cat nasal swabs from veterinary hospitals in Guangdong Province between 2018 and 2021. Six emerging H3N2 CIV strains were isolated. Following full genome sequencing and phylogenetic analyses, we found that A/canine/Guangdong/1-3/2018 and A/canine/Guangdong/1-3/2021 diverged from the reported sequences of the Chinese H3N2 CIV strains, and the phylogenetic analyses indicated that these viruses may originate from the US. These findings are cause for concern since H3N2 CIV strains that have crossed the US border to China are prevalent in Southern China.